Monocyte STAT1 phosphorylation and treatment response of JAK inhibitors in chronic nonbacterial osteomyelitis - Motoshi Sonoda; Keishiro Kinoshita; Nobutaka Harada; Sungyeon Park; Shunichi Adachi; Yutaro Yada; Katsuhide Eguchi; Toshifumi Fujiwara; Makiko Kido-Nakahara; Noriko Kinjo; Masataka Ishimura; Shouichi Ohga (Pediatric Rheumatology Online Journal)
Abstract Background Chronic nonbacterial osteomyelitis (CNO) is a rare autoinflammatory disease of unknown cause, predominantly affecting teens and young adults. The early diagnosis and management are challenging due to the lack of reliable diagnostic markers and the occasional intractable cases despite conventional anti-inflammatory treatments. Janus kinase (JAK) inhibitors have recently shown potential utility; however, reports on their use for pediatric patients with CNO remain limited, and no established biomarkers exist to monitor disease activity. We aimed to investigate the pathophysiology of CNO and explore the rapid testing methods for accurate diagnosis and also assessing the disease activity. Methods We assessed intracellular phosphorylation of signal transducer and activator of transcription 1 (pSTAT1) in peripheral blood monocytes or T cells following interferon-gamma (IFNγ) stimulation, using flow cytometry in 9 patients under 15 years old with CNO. The pSTAT1 expression levels were compared with those in patients with STAT1-gain of function (STAT1-GOF) mutations (n = 5), other autoinflammatory diseases (n = 7), and healthy controls. Clinical and immunological data were monitored in 4 patients with intractable CNO treated with adjunctive JAK inhibitors, focusing on scoring scales, imaging data, lymphocyte subsets, cytokine profiles, and pSTAT1 levels. Results Monocyte pSTAT1 expression after IFNγ stimulation was elevated at diagnosis or during active CNO, similar to levels observed in STAT1-GOF cases. The pSTAT1 levels in CNO patients were significantly higher than those in other autoinflammatory diseases (p = 0.024) or controls (p < 0.001). Notably, pSTAT1 levels in CNO monocytes fluctuated with disease activity, decreasing in 5 patients during clinical remission following conventional therapies (p = 0.016). In four intractable cases, pSTAT1 levels remained high despite conventional treatments but significantly decreased after initiating JAK inhibitors (p = 0.036). This reduction correlated with improved patient pain visual analog scale (p = 0.008), CNO clinical disease activity score (p = 0.029), and better bone and joint imaging, though cytokine levels remained unchanged. Conclusions The monocyte pSTAT1 levels after IFNγ stimulation reflect the activity of CNO, indicating the diagnostic utility as well as the monitoring effect of disease control. Adjunctive JAK inhibitors successfully controlled inflammation in treatment-resistant cases. Rapid pSTAT1 testing may help reduce osteo-articular complications, although the long-term adverse effects and resistance should be further investigated.